Meningkatkan Kepercayaan Diri Melalui Bimbingan Kelompok Remaja di Panti Asuhan Aisyiyah Kota Pariaman - Lafziatul Sasriza; Fadhilla Yusri (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The low-confidence of teenagers that occurs at the Aisyiyah orphanage in Pariaman city is a problem that is being experienced by teenagers at this orphanage. Several phenomena found also show that the self-confidence of teenagers in the low category. Based on the results of an interview with a teenager who lives in an Aisyiyah orphanage in Pariaman City, information was obtained that these teenegers want to feel attention from their parents, most of their friend look down on them, sometimes even there is discrimination from friend at school. Based on the result of research using group guidance, there was an improvement in children at the Aisyiyah Pariaman orphanage, namely first, children learned to train their self confidence. Second, have the opportunity to gain insight into various thinga around you. Third, the growth of a positive attitude of self-confidence towards oneself and the environment.